Historic Treponema pallidum genomes from Colonial Mexico retrieved from archaeological remains. - Verena J Schuenemann; Aditya Kumar Lankapalli; Rodrigo Barquera; Elizabeth A Nelson; Diana Iraíz Hernández; Víctor Acuña Alonzo; Kirsten I Bos; Lourdes Márquez Morfín; Alexander Herbig; Johannes Krause (Public Library of Science (PLoS), 2018)
Treponema pallidum infections occur worldwide causing, among other diseases, syphilis and yaws. In particular sexually transmitted syphilis is regarded as a re-emerging infectious disease with millions of new infections annually. Here we present three historic T. pallidum genomes (two from T. pallidum ssp. pallidum and one from T. pallidum ssp. pertenue) that have been reconstructed from skeletons recovered from the Convent of Santa Isabel in Mexico City, operational between the 17th and 19th century. Our analyses indicate that different T. pallidum subspecies caused similar diagnostic presentations that are normally associated with syphilis in infants, and potential evidence of a congenital infection of T. pallidum ssp. pertenue, the causative agent of yaws. This first reconstruction of T. pallidum genomes from archaeological material opens the possibility of studying its evolutionary history at a resolution previously assumed to be out of reach.